Development of an IoT-Based Smart Water System Roadmap in Singkawang City through a Comparative Study of Surabaya and Balikpapan - Brian Ernesto; Jonathan Ansell Prasetya; Kenneth Marchelino Subrata; Master Edison Siregar (Jurnal Ilmiah Sistem Informasi, 2026)
The City of Singkawang faces significant challenges in drinking water management, characterized by limited production capacity, high non-revenue water (NRW), and the absence of digital infrastructure such as AMR, LoRaWAN, and DMA, necessitating a structured development framework to support the transition toward a smart water system. This study formulates an IoT-based smart water roadmap aligned with the regional development plan (RPJMD) and the operational capacity of the local water utility through a performance gap analysis with benchmark cities (Surabaya and Balikpapan), capacity assessment using six objective parameters, and the use of secondary data from official reports and technical documents. The resulting roadmap comprises three sequential phases covering basic infrastructure reinforcement, network digitalization through IoT sensors and telemetry, and the implementation of DMA and SCADA to enable real-time monitoring and control. This approach provides a realistic and adaptive implementation framework for medium-sized cities with limited resources, strengthening NRW reduction efforts, improving service reliability, and supporting the integration of digital technologies in sustainable water utility management.